Exploring diterpene metabolism in non‐model species: transcriptome‐enabled discovery and functional characterization of labda‐7, 13E‐dienyl diphosphate synthase from Grindelia robusta. (23rd July 2015) - Zerbe, Philipp; Rodriguez, Selina M.; Mafu, Sibongile; Chiang, Angela; Sandhu, Harpreet K.; O'Neil‐Johnson, Mark; Starks, Courtney M.; Bohlmann, Jörg
Summary: Grindelia robusta or gumweed, is a medicinal herb of the sunflower family that forms a diverse suite of diterpenoid natural products. Its major constituents, grindelic acid and related grindelane diterpenoids accumulate in a resinous exudate covering the plants' surfaces, most prominently the unopened composite flower. Recent studies demonstrated potential pharmaceutical applications for grindelic acid and its synthetic derivatives. Mining of the previously published transcriptome of G. robusta flower tissue identified two additional diterpene synthases (diTPSs). We report the in vitro and in vivo functional characterization of an ent ‐kaurene synthase of general metabolism (GrTPS4) and a class II diTPS (GrTPS2) of specialized metabolism that converts geranylgeranyl diphosphate (GGPP) into labda‐7, 13 E ‐dienyl diphosphate as verified by nuclear magnetic resonance (NMR) analysis. Tissue‐specific transcript abundance of GrTPS2 in leaves and flowers accompanied by the presence of an endocyclic 7, 13 double bond in labda‐7, 13 E ‐dienyl diphosphate suggest that GrTPS2 catalyzes the first committed reaction in the biosynthesis of grindelic acid and related grindelane metabolites. With the formation of labda‐7, 13 E ‐dienyl diphosphate, GrTPS2 adds an additional function to the portfolio of monofunctional class II diTPSs, which catalytically most closely resembles the bifunctional labda‐7, 13 E ‐dien‐15‐ol synthase of the lycopod Selaginella moellendorffii . Together with a recently identified functional diTPS pair of G. robusta producing manoyl oxide, GrTPS2 lays the biosynthetic foundation of the diverse array of labdane‐related diterpenoids in the genus Grindelia . Knowledge of these natural diterpenoid metabolic pathways paves the way for developing biotechnology approaches toward producing grindelic acid and related bioproducts. Significance Statement: The family of diterpene synthase enzymes plays an important role in generating the chemical diversity of plant metabolism. We report the identification and biochemical characterization of diterpene synthases of Grindelia robusta (Asteraceae) and their role in forming an array of biologically active specialized metabolites, thus providing a deeper insight into the catalytic diversity of plant diterpene synthases and their utility for developing biotechnology platforms for plant‐derived bioproducts.